British Association of Dermatologists guidelines for the management of hidradenitis suppurativa (acne inversa) 20186. (11th March 2019) - Ingram, J.R.; Collier, F.; Brown, D.; Burton, T.; Burton, J.; Chin, M.F.; Desai, N.; Goodacre, T.E.E.; Piguet, V.; Pink, A.E.; Exton, L.S.; Mohd Mustapa, M.F.
Abstract : Linked Comment: Jemec. Br J Dermatol 2019;180 :975 . Plain language summary available online